2012
DOI: 10.1073/pnas.1220794110
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 prevents peripheral neuropathy and attenuates neuron loss in the db /db mouse, a type 2 diabetes model

Abstract: Diabetic peripheral neuropathy (DPN) is the most common complication in both type 1 and type 2 diabetes. Here we studied some phenotypic features of a well-established animal model of type 2 diabetes, the leptin receptor-deficient db − /db − mouse, and also the effect of long-term (6 mo) treatment with coenzyme Q10 (CoQ10), an endogenous antioxidant. Diabetic mice at 8 mo of age exhibited loss of sensation, hypoalgesia (an increase in mechanical threshold), and decreases in mechanical hyperalgesia, cold allody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 93 publications
2
21
1
Order By: Relevance
“…5 More recently, it was found that CoQ 10 is protective against diabetic neuropathy in animal diabetes models. 19 Our finding that the groups treated with CoQ 10 showed significantly improved motor function was consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…5 More recently, it was found that CoQ 10 is protective against diabetic neuropathy in animal diabetes models. 19 Our finding that the groups treated with CoQ 10 showed significantly improved motor function was consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…In a model of streptotozin (STZ)-treated rats, Zochodne et al reported no significant changes in DRG neuron number even 12 months after STZ (Zochodne et al, 2001). However, a recent study showed approximately 33% loss of DRG neurons in 8 month old db/db mice (Shi et al, 2013). In the present study, we found an increase in caspase-3, a protein involved in apoptotic cell death, immunoreactivity in DRG neurons of 24 week old db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…These models include partial sciatic nerve transection (Ma and Bisby, 1997), tibial transection (Hofmann et al, 2003;Garry et al, 2005), nerve crush/pinch (Villar et al, 1991;Xu et al, 2012b), and chronic nerve constriction (Villar et al, , 1991Nahin et al, 1994;Ma and Bisby, 1997;Shi et al, 1999), in which it has been suggested the extent of galanin upregulation is inversely proportional to the development of pain behavior Liu and Hökfelt, 2000) and single ligature nerve constriction (Coronel et al, 2008), partial sciatic or saphenous nerve ligation (Hulse et al, 2008), photochemically-induced ischemic nerve injury (Hao et al, 1999;Shi et al, 1999), spared nerve injury (Holmes et al, 2003), spinal nerve ligation (Fukuoka et al, 1998;Honore et al, 2000), the cisplatin model of neurotoxicity (Barajon et al, 1996), as well as after skin incision, which is preceded by inflammation (Peters et al, 2005;Hill et al, 2010). In contrast, galanin does not appear to increase in models of painful diabetic neuropathy (Zochodne et al, 2001;Burnand et al, 2004;Shi et al, 2013). After nerve injury, galanin is also increased in trigeminal (Zhang et al, 1996) and superior cervical ganglia , which may have implications in pain modulation.…”
Section: Painmentioning
confidence: 99%